Arbeitshilfe zur Bestimmung der angemessenen Aufwendungen der Unterkunft im Rahmen kommunaler Satzungen. - (:unkn) unknown (My University, 2013)
Bund und Kommunen übernehmen die angemessenen Kosten der Unterkunft und Heizung von Grundsicherungsempfängern nach SGB II und SGB XII. Seit 2011 steht mit der Satzung nach §§ 22a bis c SGB II ein Instrument zur Verfügung, die Angemessenheitskriterien für die Kosten der Unterkunft und Heizung wohnungsmarktkonform auszugestalten. Die Arbeitshilfe stellt Methoden zur Herleitung von Mietobergrenzen im Rahmen einer kommunalen Satzung vor.

The municipalities in Germany pay for the appropriate costs of housing and heating for the recipients of benefits according to the Code of Social Law (SGB) II/XII. Through the jurisdiction of the Federal Social Court and the most recent new regulation of the SGB II/XII, the requirements for the justification of the limits of appropriateness have been tightened and have become more concrete. Nevertheless, a wide range of municipal procedures exists, which is indicated in the article. One strategy in this context consists in the derivation of limits of appropriateness from the qualified rental table, another in the development of a sound concept (so-called basic security-relevant rental table) on the basis of own or outside data. In both cases a simple housing market segment must be defined, an adequate statistical measure for the analysis of the frequency distribution of the rents must be selected and the frequency/availability of appropriate dwellings must be proven. In addition to limits of appropriateness, the strategy of generalization without a further examination of the actual housing costs is possible. The differentiation of limits of appropriateness, for instance according to housing locations or energetic quality, points in the other direction. Through the statutory authorization in 22a SGB II the discussion about possible methods for the definition of appropriate housing costs will be continued.
Current municipal procedures for the regulation of the limits of appropriateness of the cost of housing.
Keywords: Wohnungswesen; Miete; Mietpreis; Mietspiegel; Wohnungsmarkt; Sozialhilfe; Berechnungsverfahren; Wohnkosten; Sozialgesetzbuch; Unterkunftskosten; Sozialleistung; Mietzuschuss; Wohngeld